CISSP certification domain 7 : security operations video boot camp 2019 - Pedersen, Thor (Packt Publishing, 2019)
"Configuring infrastructure shouldn't be painful, it should be a joy. Chef Fundamentals has been reviewed and approved by the Chef Training team. The Chef team looks forward to the development of additional Chef Courses. Chef is a platform for the DevOps workflow, and is used to automate and manage it all--infrastructure, run-time environments and applications. The most enduring and transformative companies use Chef to become fast, efficient, and innovative software-driven organizations. Join Robin Beck as he automates everything in the only Chef-Certified class. Learn to combine resources into recipes, recipes into cookbooks, and transform your infrastructure into code. With Chef we'll learn to use the power of the Ruby language to eloquently describe the state of a system, whether you're new to automation or have been administering systems since 1992. We'll learn how to locally configure a server with the Chef Development Kit, then use the power of a Chef Server to distribute your cookbook to one, or a hundred systems."--Resource description page